The commercial fishing fleet using the middle stretch of the Madeira river, Brazil - doi: 10.4025/actascibiolsci.v34i3.8119 - Renato Soares Cardoso; Carlos Edwar Carvalho Freitas (Acta Scientiarum. Biological Sciences, 2012)
Fishery resources in the Amazon region are exploited by both industrial and artisanal fishing fleets, that differ in their use of fishing gear and fishing grounds. Data on the physical characteristics of the vessels belonging to the fishing fleets using the Solimões/Amazonas river and estuaries are limited. This article presents an analysis of some physical characteristics of the commercial fishery fleet using the middle stretch of the Madeira river. Data were quantitative collected using interviews of the owners and/or skippers of fishery vessels between January 2003 and May 2004. The boats used for fishing in the region varied in size from 8 to 14 meters and had an average storage capacity ranging from 4.5 to 6.1 tons. Canoes were also used for fishing and ranged in length from 5 to 9 meters, with an average storage capacity of 0.2 tons. The results of this study demonstrate that boats in the Madeira river fleet had similar characteristics to the fishery fleet of the Solimões/Amazonas river with respect to length, use of gear, and fish storage.